Numerical investigation on heat transfer and friction factor characteristics of laminar and turbulent flow in an elliptic annulus utilizing nanofluid - Dawood, H. K. (Elsevier Ltd., 2015)
In this paper, a numerical investigation on heat transfer performance and flow fields of different nanofluids flows through elliptic annulus in a laminar and turbulent flow regimes. The three-dimensional continuity, Navier-Stokes and energy equations are solved by using finite volume method (FVM) and the SIMPLE algorithm scheme is applied to examine the effects of laminar and turbulent flow on heat transfer characteristics. This study evaluates the effects of four different types of nanoparticles, Al2O3, CuO, SiO2 and ZnO, with different volume fractions (0.5-4%) and diameters (25-80nm) under constant heat flux boundary condition using water as a base fluid were used. The Reynolds number of laminar flow was in the range of 200=Re=1500, while for turbulent flow it was in the range of 4000=Re=10,000. The results have shown that SiO2-water nanofluid has the highest Nusselt number, followed by ZnO-water, CuO-water, Al2O3-water, and lastly pure water. The Nusselt number for all cases increases with the volume fraction but it decreases with the rise in the diameter of nanoparticles. In all configurations, the Nusselt number increases with Reynolds number. It is found that the glycerine-SiO2 shows the best heat transfer enhancement compared with other tested base fluids.